ANALYSIS OF DATA LOCALIZATION IN DIGITAL MARKET INTEGRATION IN SOUTH EAST ASIAN REGION - Sitinjak, Posman Krismanto; Wahab, Riva'atul Adaniah (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2019)
The development of information and communication technology (ICT) has influenced various human life sectors, including trade. On November, Association of South East Asian Nation (ASEAN) member countries signed a cooperation framework for digital market integration as manifestation of member willingness to facilitate cross border e-commerce transaction within region. One of its concerns is trade barrier originating from digital data protection schemes applied by ASEAN states particularly data localization policy. Using the descriptive qualitative approach through literature study, this research aims to 1) introduce existing status and rationales behind digital data localization law in ASEAN countries, 2) describe possible economic implication by allowing data exchange across borders among ASEAN countries, 3) propose mechanism to address cross border data transfer issues in the perspective of regional integration theory. Results show that localization law in ASEAN member states particularly in Indonesia, Malaysia, and Singapore have different attitude but same economic motives towards cross border data transfer. Besides having positive influence on economic performance, trans-border data transfer may result in capital concentration within business-friendly territory in the condition of development disparity and may harm the existing ICT business. Thus, ASEAN could jointly established commission to develop new single regulation framework. ASEAN countries also must develop more mature ICT infrastructure and business environment in order to support the implementation of existing law. In this conditions, the role of international relation in addressing data localization issues considering various political regimes within ASEAN is needed.